NEOCATASTROPHISM: SOCIOLOGICAL REFLECTIONS UPON NEW RISKS IN THE ECOLOGICAL DOMAIN - A. Perova (Вестник университета)
The article presents a sociological analysis of the manifestations and consequences of the «new» catastrophism. It reveals arguments backing the fact that most of such catastrophes are closely tied with social, economic, political and informational life of the society. Social problems, usually associated with catastrophes, are named, which lead to a «corrosive community». The regulating role of the religion is revealed. A table, where «old» and «new» catastrophes are compared, is introduced. In conclusion, an analysis of risks, related to the «new» catastrophes is presented.